COOPERATION BETWEEN THE MAIN ACTORS IN THE SERBIAN CRIMINAL PROCEDURE - Turanjanin, Veljko M; Soković, Snežana; Čvorović, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The legislator proposed several solutions in by now not-so-new Criminal Procedure Code. They alter the criminal status of the defense attorney compared to the solutions that have been envisaged from the beginning of this century. The paper is divided into several parts. After introductory considerations, the authors consider a number of issues from the theoretical point of view, starting from collecting the evidence and materials for the defense, through cross-examination and engagement of a professional consultant in criminal proceedings, to the role of counsel. The main part of the paper is related to the results of a survey regarding practical application of new legal solutions conducted between prosecutors, defense counsels and the police. The results of the survey show that the defendant counsels use certain legal provisions, but not sufficiently.